CAMPUS-BASED MILLENNIALS’ LEARNING PREFERENCES TOWARD DA’WAH IN URBAN CITY OF SURABAYA (State Islamic University (UIN) of Sunan Ampel Surabaya, 2022)
This article aims at describing urban millennials’ preferences in learning Islam in the digital era. Since such a research project collecting data from the field is still rarely found in Indonesia, we set off to carry out the present research to address the issue. Preliminary in nature, the current study, uncovers the digital natives’ preferences toward religious da‘wah—both online and offline. Data collated from students and teachers of Islamic courses at a university in Surabaya, East Java. A total 134 people were surveyed and three people were interviewed. The results of the analysis portray the shift in learning preferences compared to those of the older generation. The millennial students choose Islamic ethics, beliefs, and jurisprudence in preference to Sufism, Islamic politics, and civilization. In addition to learning on campus, they prefer watching YouTube than reading books and attending pengajian. They were also found to prefer popular usta>dhs on YouTube as their role models.